pyfds 0.3.1 - modular field simulation tool - Claes, Leander; Webersen, Manuel

Inverses Verfahren zur Identifikation piezoelektrischer Materialparameter unterstützt durch neuronale Netze - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

On the repulsion effect of coupled Lamb wave modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Randomised material parameter impedance dataset of piezoelectric rings - Koch, Kevin; Friesen, Olga; Claes, Leander

Randomised material parameter piezoelectric impedance dataset with structured electrodes - Koch, Kevin; Claes, Leander

Investigation of change in dispersive behaviour during adhesive curing in multi-layered structures - Zeipert, Henning; von Germeten, Christian; Friesen, Olga; Claes, Leander; Johannesmann, Sarah; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)

Characterization of adhesion strength using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Phase-preserving methods to visualise ultrasonic fields with schlieren imaging - Hetkämper, Tim; Koch, Kevin; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Schlierentechnik

Improved determination of viscoelastic material parameters using a pulse-echo measurement setup - Dreiling, Dmitrij; Itner, Dominik; Hetkämper, Tim; Birk, Carolin; Gravenkamp, Hauke; Henning, Bernd (SMSI 2023 Conference)

Inverse procedure for measuring piezoelectric material parameters using a single multi-electrode sample - Claes, Leander; Feldmann, Nadine; Schulze, Veronika; Meihost, Lars; Kuhlmann, Henrik; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (Journal of Sensors and Sensor Systems)

Inverse procedure for the identification of piezoelectric material parameters supported by dense neural networks - Claes, Leander; Meihost, Lars; Jurgelucks, Benjamin

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Quantification of the adhesive coupling of layered structures using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Visualisierung von Ultraschallfeldern mittels Schlierentechnik und fraktionaler Fouriertransformation - Hetkämper, Tim

Messverfahren für die akustische Absorption zur Bestimmung der Volumenviskosität - Claes, Leander

Schlieren imaging with fractional Fourier transform to visualise ultrasonic fields - Hetkämper, Tim; Claes, Leander; Henning, Bernd (Sensoren und Messsysteme - Beiträge der 21. ITG/GMA-Fachtagung)

Identification of piezoelectric material parameters using optimised multi-electrode specimens - Claes, Leander; Feldmann, Nadine; Schulze, Veronika; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

Differentiation of an SBFE model in the context of material parameter determination - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Birk, Carolin; Henning, Bernd

Estimation of piezoelectric material parameters of ring-shaped specimens - Friesen, Olga; Claes, Leander; Feldmann, Nadine; Henning, Bernd

Lamb wave based approach to the determination of acoustic material parameters - Johannesmann, Sarah; Claes, Leander; Feldmann, Nadine; Zeipert, Henning; Henning, Bernd (tm - Technisches Messen)
Abstract In this paper a measurement procedure to identify viscoelastic material parameters of plate-like samples using broadband ultrasonic waves is presented. Ultrasonic Lamb waves are excited via the thermoelastic effect using laser radiation and detected by a piezoelectric transducer. The resulting measurement data is transformed to yield information about multiple propagating Lamb waves as well as their attenuation. These results are compared to simulation results in an inverse procedure to identify the parameters of an elastic and a viscoelastic material model.
Keywords: Electrical and Electronic Engineering; Instrumentation

Estimation of viscoelastic material parameters of polymers using Lamb waves - Johannesmann, Sarah; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Inverses Verfahren zur Bestimmung viskoelastischer Materialparameter - Johannesmann, Sarah

Quantifying the coupling strength of adhesively bonded materials by investigating mode repulsion regions - Zeipert, Henning; Johannesmann, Sarah; Nicolai, Marcel; Lugovtsova, Yevgeniya; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)

К ОПРЕДЕЛЕНИЮ ПРОЧНОСТИ КЛЕЕВОГО СОЕДИНЕНИЯ В МНОГОСЛОЙНЫХ МАТЕРИАЛАХ ПУТЕМ ИССЛЕДОВАНИЯ ОБЛАСТЕЙ РАСТАЛКИВАНИЯ БЕГУЩИХ УПРУГИХ ВОЛН - Lugovtsova, Yevgeniya; Zeipert, Henning; Johannesmann, Sarah; Nicolai, Marcel; Prager, Jens; Henning, Bernd (МАТЕМАТИЧЕСКОЕ МОДЕЛИРОВАНИЕ В ЕСТЕСТВЕННЫХ НАУКАХ - XXX Всероссийская школа-конференция)

Investigating peculiarities of piezoelectric detection methods for acoustic plate waves in material characterisation applications - Claes, Leander; Schmiegel, Hanna; Grünsteidl, Clemens; Johannesmann, Sarah; Webersen, Manuel; Henning, Bernd (tm - Technisches Messen)
Acoustic waves in plates have proven a viable tool for testing and material characterisation purposes. There are a multitude of options for excitation and detection of theses waves, such as optical and piezoelectric systems. While optical systems, with thermoelastic excitation and interferometric detection, have the benefit of being contactless, they usually require rather complex and expensive experimental setups. Piezoelectric systems are more easily realised but require direct contact with the specimen and usually have a limited bandwidth, especially in case of piezoelectric excitation. In this work, the authors compare the properties of piezoelectric and optical detection methods for broad-band acoustic signals. The shape (e. g. the displacement) of a propagating plate wave is given by its frequency and wave number, allowing to investigate correlations between mode shapes and received signal strengths. This is aided by evaluations in normalised frequency and wavenumber space, facilitating comparisons of different specimens. Further, the authors explore possibilities to utilise the specific properties of the detection methods to determine acoustic material parameters.

Simulation of guided waves in cylinders subject to arbitrary boundary conditions for applications in material characterization - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (PAMM)

Zerstörungsfreie Charakterisierung der elastischen Materialeigenschaften thermoplastischer Polymerwerkstoffe mittels Ultraschall - Webersen, Manuel
Die präzise Kenntnis der Eigenschaften verwendeter Materialien hat große Bedeutung für den Entwurf technischer Systeme aller Art, aber auch für die Überwachung solcher Systeme im Betrieb. Für verschiedene physikalische Eigenschaften, Betriebsbedingungen und Materialklassen werden daher geeignete messtechnische Verfahren zur Materialcharakterisierung benötigt. In der vorliegenden Arbeit wird ein Verfahren zur ultraschallbasierten Charakterisierung der mechanischen Eigenschaften von homogenen und faserverstärkten thermoplastischen Polymeren unter Berücksichtigung der Richtungsabhängigkeit vorgestellt. Plattenförmige Probekörper werden dazu mittels Laser-Pulsen hoher Energie breitbandig angeregt und die resultierenden akustischen Lamb-Wellen aufgezeichnet. Auf Basis der dispersiven Eigenschaften der detektierten Wellenleitermoden werden in einem inversen Verfahren die Parameter eines linear-elastischen Materialmodells identifiziert. Darüber hinaus wird ein Verfahren zur vollständigen Charakterisierung der Richtungsabhängigkeit in orthotropen Materialien wie Faserverbundwerkstoffen unter Verwendung eines zweidimensionalen Simulationsmodells vorgestellt. Das Messverfahren wird anhand einer Untersuchungsreihe an künstlich gealterten Polymer- und Faserverbundwerkstoffen verifiziert und die Übertragbarkeit der Ergebnisse auf den quasistatischen Fall betrachtet. Im Vergleich mit den Ergebnissen mechanischer Zugversuche werden die Voraussetzungen und Einschränkungen, insbesondere durch die Annahme eines ideal-elastischen Materialmodells, diskutiert.

On the forward simulation and cost functions for the ultrasonic material characterization of polymers - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd

Lamb wave based approach to the determination of elastic and viscoelastic material parameters - Johannesmann, Sarah; Claes, Leander; Henning, Bernd (tm - Technisches Messen)

Measurement and Simulation of Lamb Waves in Adhesive-bonded Multilayer Systems - Zeipert, Henning; Claes, Leander; Johannesmann, Sarah; Webersen, Manuel; Lugovtsova, Yevgeniya; Prager, Jens; Henning, Bernd

Measurement procedure for acoustic absorption and bulk viscosity of liquids - Claes, Leander; Chatwell, René Spencer; Baumhögger, Elmar; Hetkämper, Tim; Zeipert, Henning; Vrabec, Jadran; Henning, Bernd (Measurement)

An approach to adhesive bond characterisation using guided acoustic waves in multi-layered plates - Zeipert, Henning; Claes, Leander; Johannesmann, Sarah; Lugovtsova, Yevgeniya; Nicolai, Marcel; Prager, Jens; Henning, Bernd (at - Automatisierungstechnik)
An approach for the non-destructive characterisation of adhesive bonds using guided ultrasonic waves is presented. Pulsed laser radiation is used to thermoacoustically excite broadband ultrasonic waves in a multi-layered sample, consisting of a metal plate adhesively joined to a polymeric layer using synthetic resin. The resulting signals are received by a purpose-built piezoelectric transducer. Varying the distance between excitation and detection yields spatio-temporal measurement data, from which the dispersive properties of the propagating waves can be inferred using a two-dimensional Fourier transform, assuming the plates to act as coupled waveguides. Coupled multi-layered waveguides show an effect referred to as mode repulsion , where the distance between certain modes in the frequency-wavenumber domain is assumed to be a measure of coupling strength. Measurements at different stages of curing of the adhesive layer are performed and evaluated. A comparison of the results shows changes in the dispersive properties, namely an increased modal bandwidth for the fully cured sample as well as an increased modal distance.

Tomographie des Schallfelds von Ultraschallwandlern mittels Schlierentechnik - Hetkämper, Tim; Dreiling, Dmitrij; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)

Application and modelling of ultrasonic transducers using 1-3 piezoelectric composites with structured electrodes - Dreiling, Dmitrij; Itner, Dominik; Feldmann, Nadine; Scheidemann, Claus; Gravenkamp, Hauke; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)
Waveguide-based methods can be used for the non-destructive determination of acoustic material parameters. One of these methods is based on transmission measurements of cylindrical polymeric specimens. Here, the experimental setup consists of two transducers, which excite and receive the waveguide modes at the faces of the cylinder. The measurement, as well as a forward model, are used to determine material parameters of the polymeric specimen in an inverse approach. 1-3 piezoelectric composites are used as an active element because they can be approximated by a thickness vibration only. This allows an easy identification of Mason model parameters to characterise the transducers’ vibration behaviour. However, sensitivity analysis shows a high uncertainty in the determination of the mechanical shear parameters due to the uniform excitation. To increase the sensitivity to these shear motions, arbitrary excitations were investigated by means of numerical simulation. In order to be able to realise the determined optimal excitation, new transducer prototypes were designed. By subdividing the electrodes of the active element, for example, ring-shaped excitation is feasible. Furthermore, it can be shown that modelling these transducers with a one-dimensional Mason model is sufficient.

Messverfahren für die akustische Absorption in reinen Fluiden zur Bestimmung der Volumenviskosität - Claes, Leander
Die vollständige Beschreibung fluiddynamischer und akustischer Vorgänge setzt voraus, dass die Eigenschaften des Fluids hinlänglich bekannt sind.Während Fluidkenngrößen, wie etwa die Schallgeschwindigkeit oder die Scherviskosität, für viele Flüssigkeiten über weite Bereiche des thermodynamischen Zustandsraums bekannt sind, existieren für die Volumenviskosität nur eine geringe Anzahl Messdaten.In dieser Arbeit wird daher ein Messverfahren zur selektiven Bestimmung der Volumenviskosität von Flüssigkeiten, basierend auf der Absorption von Ultraschallwellen, entwickelt und realisiert.Schwerpunkte bilden dabei der simulationsgestützte Entwurf von Algorithmen zur Auswertung der Messsignale sowie die Analyse und Weiterentwicklung einer Messanordnung, basierend auf dem Puls-Echo-Verfahren. Neben der Absorption im Fluid treten dabei weitere Effekte (zum Beispiel Beugung oder unvollständige Reflexion) auf, die das akustische Signal schwächen oder anderweitig beeinflussen. Die Entwicklung von Verfahren zur Trennung dieser Effekte von der akustischen Absorption bildet daher einen weiteren Schwerpunkt dieser Arbeit.Abschließend wird die Volumenviskosität aus der gemessenen akustischen Absorption für unterschiedliche Fluide in verschiedenen thermodynamischen Zuständen unter Zuhilfenahme anderer bekannter Fluidkenngrößen bestimmt sowie eine Unsicherheitsbetrachtung durchgeführt.

Optimal experiment design with respect to electrode configurations for a piezoelectric problem - Schulze, Veronika; Schmidt, Stephan; Jurgelucks, Benjamin; Feldmann, Nadine; Claes, Leander

Modelling damping in piezoceramics: A comparative study - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The progress in numerical methods and simulation tools promotes the use of inverse problems in material characterisation problems. A newly developed procedure can be used to identify the behaviour of piezoceramic discs over a wide frequency range using a single specimen via fitting simulated and measured impedances by optimising the underlying material parameters. Since there is no generally accepted damping model for piezoelectric ceramics, several mechanical damping models are examined for the material identification. Three models have been chosen and their ability to replicate the measured impedances is evaluated. On the one hand, the common Rayleigh model is considered as a reference. On the other hand, a Zener model and a model using complex constants are extended to model the transversely isotropic material. As the Rayleigh model is only valid for a limited frequency range, it fails to model the broadband behaviour of the material. The model using complex constants leads to the best fit over a wide frequency range while at the same time only adding three additional parameters for modelling damping. Thus, damping can be assumed approximately frequency-independent in piezoceramics.

Optimised Multi-Electrode Topology for Piezoelectric Material Characterisation - Claes, Leander; Feldmann, Nadine; Jurgelucks, Benjamin; Schulze, Veronika; Schmidt, Stephan; Walther, Andrea; Henning, Bernd

Piezoelectric BC Modeling for Electrode Shapes with OED - Schulze, Veronika; Schmidt, Stephan; Jurgelucks, Benjamin; Feldmann, Nadine; Claes, Leander

Simulation of Guided Waves in Cylinders Subject to Arbitrary Boundary Conditions Using the Scaled Boundary Finite Element Method - Itner, D.; Gravenkamp, H.; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (14th WCCM-ECCOMAS Congress)

Efficient semi-analytical simulation of elastic guided waves in cylinders subject to arbitrary non-symmetric loads - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (Ultrasonics)

Ein modellbasiertes Messverfahren zur Charakterisierung von Piezokeramiken unter Verwendung eines einzelnen scheibenförmigen Probekörpers - Feldmann, Nadine
Designprozesse von Schallwandlern werden durch zunehmende Rechenkapazitäten immer mehr durch simulative Betrachtungen unterstützt. Dabei ist vor allem die Wahl der Materialparameter der verwendeten Materialien wichtig für ein realitätsnahes Simulationsergebnis. Bei Schallwandlern werden häufig Piezokeramiken als aktive Elemente genutzt, welche sich durch eine Verkopplung mechanischer und elektrischer Eigenschaften auszeichnen. Zur Bestimmung ihrer Materialparameter stellt der IEEE Standard on Piezoelectricity ein standardisiertes Verfahren dar. Dazu sind fünf Impedanzmessungen an vier unterschiedlich gefertigten Probekörpergeometrien notwendig. Da an jedem einzelnen Probekörper nur eine Untermenge aller notwendigen Materialparameter bestimmt werden kann, werden diese dann zu einem kompletten Materialparametersatz zusammengefügt. Aufgrund der unterschiedlichen Prozessbedingungen, bei denen die jeweiligen Probekörper hergestellt werden, ist dieser Materialparametersatz jedoch inkonsistent und kann nie das Verhalten einer einzelnen Probe beschreiben. Daher wird in der vorliegenden Arbeit ein Messverfahren entwickelt, mit dem es möglich ist, alle relevanten Materialparameter unter besonderer Berücksichtigung von Dämpfung an einem einzelnen Probekörper allein durch Impedanzmessungen zu bestimmen. Als Probekörper wird dazu eine in der Anwendung häufig verwendete Scheibengeometrie verwendet. Um eine hinreichend hohe Sensitivität auf alle Materialparameter zu gewährleisten, wird diese mit einer optimierten Elektrodentopologie gefertigt. Da in diesem Fall keine analytische Betrachtung mehr möglich ist, wird das Messverfahren durch einen inversen Ansatz realisiert.

The Influence of Hydrothermal Aging on the Material Properties of Continuous Fiber-Reinforced Thermoplastics and its Non-Destructive Characterization - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Advances in Polymer Processing 2020)